Penerapan Model Pembelajaran Kooperatif Tipe Team Game Tournament (TGT) untuk Meningkatkan Aktivitas dan Hasil Belajar Sejarah Siswa Kelas XI IPS-1 SMAN 1 Rantau Kobar - Gustina Gustina (Journal on Education, 2022)
This study aims to obtain information and discuss the application of cooperative learning models of the team game tournament (TGT) type to increase the activity and results of learning history for class XI IPS-1 SMAN 1 Rantau Kobar. This research is a classroom action research which is a systematic study conducted in order to improve practices in education so that student learning outcomes are further enhanced by taking practical actions in reflection and action. Classroom action research is an activity that consists of a series of activities, in this study there are several cycles. The cycle will be stopped when learning completeness has been fulfilled. The four main activities in each cycle are planning, implementing, observing, and reflecting. This research was conducted at SMAN 1 Rantau Kobar. The subjects in this study were students of SMAN 1 Rantau Kobar. Data collection techniques used observation sheets, tests, field notes and documentation. Data were analyzed using percentages and data reduction. Based on the results of the research and discussion, it can be concluded that the activities and results of student history learning increased through the cooperative learning model of the team game tournament (TGT) type for class XI IPS-1 students of SMAN 1 Rantau Kobar.